An experimental study of basaltic glass-H2O-CO2 interaction at 22 and 50°C: Implications for subsurface storage of CO2 - Galeczka, I.; Wolff-Boenisch, Domenik; Oelkers, E.; Gislason, S. (Pergamon, 2014)
A novel high pressure column flow reactor was used to investigate the evolution of solute chemistry along a 2.3 m flow path during pure water- and CO2-charged water–basaltic glass interaction experiments at 22 and 50 °C and 10−5.7 to 22 bars partial pressure of CO2. Experimental results and geochemical modelling showed the pH of injected pure water evolved rapidly from 6.7 to 9–9.5 and most of the iron released to the fluid phase was subsequently consumed by secondary minerals, similar to natural meteoric water–basalt systems. In contrast to natural systems, however, the aqueous aluminium concentration remained relatively high along the entire flow path. The aqueous fluid was undersaturated with respect to basaltic glass and carbonate minerals, but supersaturated with respect to zeolites, clays, and Fe hydroxides. As CO2-charged water replaced the alkaline fluid within the column, the fluid briefly became supersaturated with respect to siderite. Basaltic glass dissolution in the column reactor, however, was insufficient to overcome the pH buffer capacity of CO2-charged water. The pH of this CO2-charged water rose from an initial 3.4 to only 4.5 in the column reactor.This acidic reactive fluid was undersaturated with respect to carbonate minerals but supersaturated with respect to clays and Fe hydroxides at 22 °C, and with respect to clays and Al hydroxides at 50 °C. Basaltic glass dissolution in the CO2-charged water was closer to stoichiometry than in pure water. The mobility and aqueous concentration of several metals increased significantly with the addition of CO2 to the inlet fluid, and some metals, including Mn, Cr, Al, and As exceeded the allowable drinking water limits. Iron became mobile and the aqueous Fe2+/Fe3+ ratio increased along the flow path. Although carbonate minerals did not precipitate in the column reactor in response to CO2-charged water–basaltic glass interaction, once this fluid exited the reactor, carbonates precipitated as the fluid degassed at the outlet. Substantial differences were found between the results of geochemical modelling calculations and the observed chemical evolution of the fluids during the experiments. These differences underscore the need to improve the models before they can be used to predict with confidence the fate and consequences of carbon dioxide injected into the subsurface.